Corrigendum to “Human biomonitoring guidance values (HBM-GVs) for priority substances under the HBM4EU initiative – New values derivation for deltamethrin and cyfluthrin and overall results” [Int. J. Hyg. Environ. Health 248 (2023) 114097] - P. Apel; F. Lamkarkach; R. Lange; F. Sissoko; M. David; C. Rousselle; G. Schoeters; M. Kolossa-Gehring (International Journal of Hygiene and Environmental Health, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Human biomonitoring guidance values (HBM-GVs) for priority substances under the HBM4EU initiative – New values derivation for deltamethrin and cyfluthrin and overall results - P. Apel; F. Lamkarkach; R. Lange; F. Sissoko; M. David; C. Rousselle; G. Schoeters; M. Kolossa-Gehring (International Journal of Hygiene and Environmental Health, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Cuphea spp.: antichemotactic study for a potential anti-inflammatory drug - Marí C. Santos; Krissie D. Soares; Betina M. Beltrame; Sérgio A. L. Bordignon; Miriam A. Apel; Andreas S. L. Mendez; Amélia T. Henriques (Natural Product Research, 2021)

Temporary threshold shift after noise exposure in hypobaric hypoxia at high altitude: results of the ADEMED expedition 2011 - K. Fehrenbacher; C. Apel; D. Bertsch; M. S. van der Giet; S. van der Giet; M. Grass; C. Gschwandtl; N. Heussen; N. Hundt; C. Kühn; A. Morrison; M. Müller-Ost; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives To evaluate whether there is an increased risk for noise-induced hearing loss at high altitude rsp. in hypobaric hypoxia. Methods Thirteen volunteers got standard audiometry at 125, 250, 500, 750, 1000, 1500, 2000, 3000, 4000, 6000, and 8000 Hz before and after 10 min of white noise at 90 dB. The system was calibrated for the respective altitude. Measurements were performed at Kathmandu (1400 m) and at Gorak Shep (5300 m) (Solo Khumbu/Nepal) after 10 days of acclimatization while on trek. Temporary threshold shift (TTS) was analyzed by descriptive statistics and by factor analysis. Results TTS is significantly more pronounced at high altitudes. Acclimatization does not provide any protection of the inner ear, although it increases arterial oxygen saturation. Conclusion The thresholds beyond which noise protection is recommended (> 80 dB) or necessary (> 85 dB) are not sufficient at high altitudes. We suggest providing protective devices above an altitude of 1500 m (“ear threshold altitude”) when noise level is higher than 75 dB and using them definitively above 80 dB. This takes the individual reaction on hypobaric hypoxia at high altitude into account.

Guanosine Neuroprotection of Presynaptic Mitochondrial Calcium Homeostasis in a Mouse Study with Amyloid-β Oligomers - Jussemara Souza da Silva; Yasmine Nonose; Francieli Rohden; Pâmela C. Lukasewicz Ferreira; Fernanda Urruth Fontella; Andréia Rocha; Andressa Wigner Brochier; Rodrigo Vieira Apel; Thais Martins de Lima; Bianca Seminotti; Alexandre Umpierrez Amaral; Antonio Galina; et al. (Molecular Neurobiology, 2020)

Unique isoprene oxidation products demonstrate chlorine atom chemistry occurs in the Houston, Texas urban area - Daniel D. Riemer; Eric C. Apel; John J. Orlando; Geoffrey S. Tyndall; William H. Brune; Eric J. Williams; William A. Lonneman; James D. Neece (Journal of Atmospheric Chemistry, 2008)

Depressive symptoms, quality of life, and neuropsychological performance in HIV/AIDS: The impact of gender and injection drug use - Amy B Wisniewski; Samantha Apel; Ola A. Selnes; Avindra Nath; Justin C McArthur; Adrian S. Dobs (Journal of NeuroVirology, 2005)

Quality Assurance of Hydrocarbon Measurements for the German Tropospheric Research Focus (TFS) - A. Volz-Thomas; J. Slemr; S. Konrad; Th. Schmitz; E. C. Apel; V. A. Mohnen (Journal of Atmospheric Chemistry, 2002)

Simple sequence repeat (SSR) markers survey of the cassava (Manihot esculenta Crantz) genome: towards an SSR-based molecular genetic map of cassava - R. E. C. Mba; P. Stephenson; K. Edwards; S. Melzer; J. Nkumbira; U. Gullberg; K. Apel; M. Gale; J. Tohme; M. Fregene (Theoretical and Applied Genetics, 2001)